Effects of the financial crisis and Troika austerity measures on health and health care access in Portugal - Legido-Quigley, H. (2016)
Although Portugal has been deeply affected by the global financial crisis, the impact of the recession and subsequent austerity on health and to health care has attracted relatively little attention. We used several sources of data including the European Union Statistics for Income and Living Conditions (EU-SILC) which tracks unmet medical need during the recession and before and after the Troika's austerity package. Our results show that the odds of respondents reporting having an unmet medical need more than doubled between 2010 and 2012 (OR=2.41, 95% CI 2.01-2.89), with the greatest impact on those in employment, followed by the unemployed, retired, and other economically inactive groups. The reasons for not seeking care involved a combination of factors, with a 68% higher odds of citing financial barriers (OR=1.68, 95% CI 1.32-2.12), more than twice the odds of citing waiting times and inability to take time off work or family responsibilities (OR 2.18, 95% CI 1.20-3.98), and a large increase of reporting delaying care in the hope that the problem would resolve on its own (OR=13.98, 95% CI 6.51-30.02). Individual-level studies from Portugal also suggest that co-payments at primary and hospital level are having a negative effect on the most vulnerable living in disadvantaged areas, and that health care professionals have concerns about the impact of recession and subsequent austerity measures on the quality of care provided. The Portuguese government no longer needs external assistance, but these findings suggest that measures are now needed to mitigate the damage incurred by the crisis and austerity.